Novas possibilidades para o ensino da língua materna - Jorgens, Denise (Linguagens & Cidadania, 2017)
Vygotsky proposes the teacher to be an instrument to the knowledge searching, interacting with the student, making the most of the knowledge he brings to the classroom, and giving opportunity to the student developing through his thinking and his capacity, that he learns searching the answers, building his information through the elements given in class, getting to think the content with his reality. In this sense, it was verified the importance to develop on the student his communication abilities, mainly on the Portuguese Language classes, proportioning a cooperative ambient, through the information exchange, in order to participate on the educational process.